2019
DOI: 10.20489/intjecse.512378
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Of Parent Training A Mothers Of Children With Autism Use Of Mand Model Techniques

Abstract: The present study examined the effectiveness of the parent training program that was designed for the mothers of children with Autism Spectrum Disorders in enabling them to use the mand-model procedure. The study was conducted with the participation of 3 boys with Autism Spectrum Disorders and their mothers. As part of the study, the mothers were taught the mand-model procedure, which is one of the milieu teaching techniques. As a research method, the present study employed the subject research models of betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Aktas [27] studied the impact of teaching mothers of children with ASD the use of mand model technique to improve language skills in children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aktas [27] studied the impact of teaching mothers of children with ASD the use of mand model technique to improve language skills in children.…”
Section: Resultsmentioning
confidence: 99%
“…The content of the intervention or training programs differed, most of them concentrated on enhancing communication between the parent / caregiver and the child [27], decreasing maladaptive behaviors in the child, and establishment of daily routines. Psycho-education of ASD was the most common component found across studies.…”
Section: Study Themesmentioning
confidence: 99%
“…Results revealed that the interventions significantly increased the mand repertoire of both children and that the technological solution facilitated the collection of reliable data not only by experienced therapists but also by caregivers in the home contest. As pointed out in the literature ( Aktaş and Ciftci-Tekinarslan, 2018 ), this generalization seems to have been facilitated by the active participation of the carers, trained through careful parent training both to implement the procedure and to record the data with BEHAVE application, which made their collection easier. The BEHAVE application has facilitated the gathering of data in various contexts and the sharing of the results between the various figures involved.…”
Section: Discussionmentioning
confidence: 99%
“…Em 87 % dos estudos (n = 15) que avaliaram a aprendizagem de aplicadores de ensino de mando, as intervenções foram totalmente efetivas (e.g., Loughrey et al, 2014). As intervenções também se mostraram totalmente efetivas em: (1) dois de três estudos que avaliaram a manutenção das respostas adquiridas (Aktas & Ciftci-Tekinarslan, 2018;McCulloch & Noonan, 2013); e (2) no único estudo em que foi identificada avaliação de generalização do repertório aprendido (Nigro-Bruzzi & Sturmey, 2010).…”
Section: Avaliação Da Efetividade Das Intervençõesunclassified